Barriers and facilitators for engagement and implementation of exercise in end‐stage kidney disease: Future theory‐based interventions using the Behavior Change Wheel. Issue 4 (1st April 2019) - Clarke, Amy L.; Jhamb, Manisha; Bennett, Paul N.
Abstract: Theory‐driven interventions are required to increase the adoption and implementation of physical activity and exercise programs among patients with ESKD. The Behavior Change Wheel (BCW) represents a synthesis of behavior change theories and can be used to aid the systematic development of theory‐driven interventions designed to change exercise behavior. The goal of this review was to synthesize barriers and facilitators to engagement and implementation of exercise and develop theory‐based recommendations for exercise behavior change interventions in patients with ESKD. We applied the BCW in the current context of exercise for ESKD patients and conducted an analysis of patients' and health care professionals' (HCPs) capabilities, opportunities, and motivations to engage or promote exercise, respectively. Our analysis identified a number of salient barriers that could be targeted via intervention to increase levels of physical activity and exercise. Intervention functions identified as most likely to change patient behavior included training, enablement, education, restructuring environment, persuasion, modeling, incentivizing, and coercion. Similarly, intervention functions most likely to change HCPs behavior for exercise promotion included training, modeling, education, environmental restructuring, persuasion, and incentivizing. We also considered potential over‐arching policy changes required to support these interventions. Our findings provide theory‐based recommendations that can help inform future clinical and research decision‐making for implementing exercise interventions in these patients. However, high‐quality research in this area is desperately needed to ensure that interventions not only be theory‐driven, but evidence‐based.